Beyond Barker: Infant Mortality at Birth and Ischaemic Heart Disease in Older Age - Samuel Baker; Pietro Biroli; Hans van Kippersluis; Stephanie von Hinke Kessler Scholder (Institute of Labor Economics (IZA), 2022)
Adverse conditions in early life can have consequential impacts on individuals' health in older age. In one of the first papers on this topic, Barker and Osmond (1986) show a strong positive relationship between infant mortality rates in the 1920s and ischaemic heart disease in the 1970s. We go 'beyond Barker', first by showing that this relationship is robust to the inclusion of local geographic area fixed effects, but not family fixed effects. Second, we explore whether the average effects conceal underlying heterogeneity: we examine if the infant mortality effect offsets or reinforces one's genetic predisposition for heart disease. We find considerable heterogeneity that is robust to within-area as well as within-family analyses. Our findings show that the effects of one's early life environments mainly affect individuals with the highest genetic risk for developing heart disease. Put differently, in areas with the lowest infant mortality rates, the effect of one's genetic predisposition effectively vanishes. These findings suggests that advantageous environments can cushion one's genetic risk of developing heart disease.
Keywords: I10; I14; I19; 330; gene-environment interplay; developmental origins; Barker hypothesis